Optimization of tribological behavior of magnesium metal-metal composite using pattern search and simulated annealing techniques. (2020) - Sathish, S.; Anandakrishnan, V.; Gupta, Manoj
Abstract: Magnesium based metal-metal composite was synthesized through the disintegrated melt deposition technique with the inclusion of aluminium and titanium powders. To examine the metallurgical features of the metal-metal composite the samples of the produced composite was subjected to x-ray diffraction analysis and scanning electron microscopy analysis. To study the tribology of the metal-metal composite, pins of composites were subjected to dry sliding wear test as per standards and the specific wear and the coefficient of friction was taken as response variables. Two different computational techniques such as pattern search and simulated annealing was used to identify the optimal values of specific wear and coefficient of friction along with the identification of optimal parameter combinations. The optimum values of specific wear and coefficient of friction obtained from the pattern search technique is found to be closer to the calculated values compared to the simulated annealing technique.